Linguistic Analysis: Representation of Women in the Discourse of Presidential and Vice-Presidential Candidates in Political News - Suhartina, Suhartina (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
This research aims to elucidate the construction of symbolic meaning within the discourse of women through Fairclough's analysis of online news. The research method employed a qualitative approach with critical discourse analysis techniques, utilizing instruments devised by the researcher. Data were collected through documentation methods, identifying auxiliary/modal verbs, verbs, nouns, adjectives, conjunctions, nominal phrases, and numeral phrases within the text. Findings revealed a linguistic hierarchy reflecting gender equality ideology and the distribution of political power. Representations through word and phrase choices depicted male dominance in Indonesian politics, efforts to enhance women's roles in policy structures, and hopes to win elections with strong support. This analysis aids in understanding how women's discourse is shaped and influences perceptions and actions in daily communication. Through this article, it is anticipated that awareness regarding language usage to strengthen gender equality will increase, emphasizing the continual need to expand women's participation in shaping political policies.